Determinação dos efeitos da escolha do modelo chuva-vazão e da discretização em sub-bacias nos resultados da vazão máxima de hidrogramas e volumes de armazenamento de bacias de detenção. - Silveira Neto, José Paulo da (2021)
Unplanned urbanization processes led to significant impacts on rainwater drainage, it increased particularly flood frequency and intensity. Flood cont:rol in urban centers includes different solutions as detention basins. The present study aims to investigate how choosing between SWMM and HU-NRCS hydrnlogical models, as well as spatial discretization of the drainage basin, affects the computation of maximum discharge in the design hydrographs and the volume of detention basins. For this purpose, a software with a graphical user interface was developed. It enables the definition of physical and hydrological parameters of drainage basins (including its boundaries), hydrological simulation using HU-NRCS model, and flood propagation simulation using the dynamic wave method. It was applied to five sub-basins in the city of Teresina, Piauí, Brazil anda sensitivity analysis was conducted, varying basin area, CN, length and slope of the main river, time of concentration, and design rainfall duration time. Basin area and CN were the most imp01tant parameters when determining maximum discharge in the design hydrographs and the volume of the detention basins. These results were compared to a SWMM rainfall-mnoff t:ransfonnation model. Differences between thei:r results were dependent on drainage basin a:rea and rainfall duration time. ln small basins (A :S 10.00 km2 with extended rainfall duration (720 min), the HU-NRCS model results in larger peak flows. Similarly, for the volume of the detention basins, the values calculated by the HU-NRCS model are larger than those calculated by the SWMM model. Regarding the evaluation of discretization effects, six levels of spatial discretization for a drainage basin were analyzed. The higher the level of discretization was, the lower were the values computed for the maximum discharge in the design hydrographs and the volume of the detention basins.